Environmental Tax Reform and Producer Foresight: An Intertemporal Computable General Equilibrium Analysis - Brita Bye (Statistics Norway, Research Department, 1996)
This paper analyses the non-environmental welfare costs of an environmental tax reform using a numerical intertemporal general equilibrium model for the Norwegian economy. The tax reform is revenue neutral such that an increase in the carbon tax rate is accompanied by a reduction in the payroll tax. By exploiting existing tax wedges in the labour market and between consumption and saving, the total non-environmental welfare effect of the tax reform is positive. The paper also analyses how imperfect price expectations for the investors in real capital influence the total welfare costs of the tax reform. The welfare effect is the same due to exploitation of initial distortions, but the transitional dynamics are quite different in the two paths.
Keywords: C68; D58; D60; D90; H20; Q43; 330; Dynamic general equilibrium analysis; Environmental tax reforms; Imperfect expectations.